In vivo positron emission tomography imaging of mitochondrial abnormalities in a mouse model of tauopathy - Barron, Anna M. (2023)
Damaged mitochondria may be one of the earliest manifestations of Alzheimer`s disease (AD). Since oxidative phosphorylation is a primary source of neuronal energy, unlike glycolysis-dependent energy production in inflamed glia, mitochondrial respiration could provide a selective biomarker of neuronal deterioration in AD. Here we used a recently developed positron emission tomography (PET) probe targeting mitochondrial complex I (MC-I), 18F-BCPP-EF, to non-invasively visualize mitochondrial abnormalities in the brains of tau transgenic mice (rTg4510 TauTg). Tauopathy and neuroinflammation were visualized by PET using a tau probe 11C-PBB3 and a TSPO probe, 18F-FEBMP, respectively. A marked reduction in 18F-BCPP-EF uptake was observed in hippocampal and forebrain regions of TauTg mice, colocalizing with regions of tauopathy, neuronal damage and neuroinflammation. MC-I signals were highly correlated with atrophy assayed by MRI, but negatively associated with inflammatory signals measured by TSPO-PET, indicating that neuronal metabolic signals measured by MC-I PET were robust to inflammatory interference. MC-I may be a useful imaging biomarker to detect neuronal damage and metabolic changes with minimal interference from concomitant glial hypermetabolism.